2013
DOI: 10.1186/1479-5868-10-101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the association between childhood overweight and obesity and primary school diet and physical activity policies

Abstract: Obesity is a major public health concern and there are increasing calls for policy intervention. As obesity and the related health conditions develop during childhood, schools are being seen as important locations for obesity prevention, including multifaceted interventions incorporating policy elements. The objective of this systematic review was to evaluate the effects of policies related to diet and physical activity in schools, either alone, or as part of an intervention programme on the weight status of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 48 publications
4
88
0
4
Order By: Relevance
“…38 Some authors claim for longer follow-ups, which would allow assessing whether the changes last over time. [32][33][34][35][36][37][38][39][40][41] Regarding intervention characteristics, most reviews report actions based on nutritional education. While leaflets or two-hour activities can improve knowledge, they have not shown to modify behaviours sustainably.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38 Some authors claim for longer follow-ups, which would allow assessing whether the changes last over time. [32][33][34][35][36][37][38][39][40][41] Regarding intervention characteristics, most reviews report actions based on nutritional education. While leaflets or two-hour activities can improve knowledge, they have not shown to modify behaviours sustainably.…”
Section: Resultsmentioning
confidence: 99%
“…However, more research is needed to confirm this hypothesis. [35][36][37][38][39][40][41][42][43] In addition, particularly at young ages, habit changes do not directly depend on children but rather on the adults in their environment, principally parents, but also other relatives, neighbors, teachers, and canteen educators. As expected, family involvement emerges as a crucial aspect [36][37][38][39][40][41][42][43][44][45][46][47][48] although a remaining major question concerns how they should be involved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This view is reinforced by other research using data from the NCMP that suggested that there was no consistent school effect on childhood obesity. 143 Future studies need to develop interventions that aim to specifically affect the family environment, perhaps employing a more widely co-ordinated whole-systems approach, although it is unlikely that such an approach would be feasible to deliver within a school setting.…”
Section: Research Recommendationsmentioning
confidence: 99%
“…Igualmente, en varias revisiones sistemáticas se ha señalado la necesidad de desarrollar políticas que fomenten el ejercicio físico, con el objetivo de aumentar la masa libre de grasa, mantener un peso corporal saludable y prevenir enfermedades en niños y jóvenes (18,19). A pesar de los avances en la divulgación de información y de las campañas y políticas públicas de prevención de la obesidad y de promoción de estilos de vida saludables y activos, en la sociedad actual se evidencia una elevada inactividad física, que ya se considera un problema de salud pública a escala global y que se perfila como el mayor del siglo XXI (20)(21)(22).…”
unclassified